1972
DOI: 10.1021/jf60181a019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking on selenium content of foods

Abstract: The amount of the individual alkaloids present in the smoke compared with that in the leaf is reflected by the percent transfer data. With the UK Reference Cigarette, the high and low extremes for nicotine delivery were 24.2 and 9.8%, respectively. For nornicotine these respective extremes were 15.4 and 7.7%; for anabasine they were 38.2 and 10.2%, and for anatabine the high and low extremes were 8.4 and 2.7%. With the commercial cigarette, percentage of nicotine transferred ranged from 22.8% to 6.7%. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…Other studies on seafood also report high retention of selenium during cooking. Based on dry weight calculation, baking of flounder fillets wrapped in aluminium foil caused no consistent losses of selenium [36]. The effect of cooking has been studied for tuna and no significant difference (P \ 0.05) in total selenium concentration was found before and after cooking [35].…”
Section: Selenium and Faamentioning
confidence: 99%
“…Other studies on seafood also report high retention of selenium during cooking. Based on dry weight calculation, baking of flounder fillets wrapped in aluminium foil caused no consistent losses of selenium [36]. The effect of cooking has been studied for tuna and no significant difference (P \ 0.05) in total selenium concentration was found before and after cooking [35].…”
Section: Selenium and Faamentioning
confidence: 99%
“…Selenium content can also vary as a consequence of the technological processes used for food production and pro cessing such as milling, blanching, cooking, etc. [4,5], Reported selenium losses from the mill ing processes are due to the removal, from of Se for GSHPx synthesis in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that food processing such as boiling or roasting could decrease the Se content by leaching or volatilization . Navarro‐Alarcon and Cabrera‐Vique reported that, during 20 min of boiling, asparagus and mushrooms lost 29% and 44% of their original Se content, respectively, although no details of the boiling procedure were provided . Probably Se was leached into the cooking water .…”
Section: Resultsmentioning
confidence: 99%